Analysis Project-Based Learning of English Speaking Skills in Merdeka Curriculum - Damayanti, Yasri Tika (DUTIES: Education and Humanities International Journal, 2025)
This qualitative study explores the perceptions of teachers and 10th-grade students in senior high school on the use of Project-Based Learning (PjBL) to improve English- speaking skills within the Merdeka Curriculum. Data were collected through interviews, observations, and document analysis. Teachers observed that PBL effectively enhances student engagement, collaboration, and speaking confidence, though they noted challenges such as time constraints and varying English proficiency levels. Students reported that PjBL increased their confidence and motivation, as it allowed for self- expression and interactive learning. Classroom observations showed that PjBL promoted active student participation, with teachers facilitating and providing feedback on speaking skills. Document analysis highlighted improvements in students' creativity and vocabulary usage, despite occasional grammar issues. The study concludes that PBL, aligned with the Merdeka Curriculum, fosters English-speaking skills and encourages active learning, though additional support is needed to address challenges in collaboration and classroom management.